Public cardiopulmonary resuscitation training rates and awareness of hands‐only cardiopulmonary resuscitation: a cross‐sectional survey of Victorians. (13th January 2017) - Bray, Janet E; Smith, Karen; Case, Rosalind; Cartledge, Susie; Straney, Lahn; Finn, Judith
Abstract: Objectives: To provide contemporary Australian data on the public's training in cardiopulmonary resuscitation (CPR) and awareness of hands‐only CPR. Methods: A cross‐sectional telephone survey in April 2016 of adult residents of the Australian state of Victoria was conducted. Primary outcomes were rates of CPR training and awareness of hands‐only CPR. Results: Of the 404 adults surveyed (mean age 55 ± 17 years, 59% female, 73% metropolitan residents), 274 (68%) had undergone CPR training. Only 50% ( n = 201) had heard of hands‐only CPR, with most citing first‐aid courses (41%) and media (36%) as sources of information. Of those who had undergone training, the majority had received training more than 5 years previously (52%) and only 28% had received training or refreshed training in the past 12 months. Most received training in a formal first‐aid class (43%), and received training as a requirement for work (67%). The most common reasons for not having training were: they had never thought about it (59%), did not have time (25%) and did not know where to learn (15%). Compared to standard CPR, a greater proportion of respondents were willing to provide hands‐only CPR for strangers (67% vs 86%, P < 0.001). Conclusion: From an Australian perspective, there is still room for improvement in CPR training rates and awareness of hands‐only CPR. Further promotion of hands‐only CPR and self‐instruction (e.g. DVD kits or online) may see further improvements in CPR training and bystander CPR rates.